Oral Rinse as a Simpler Approach to Exfoliative Cytology: A Comparative Study - Shaila Mulki; Pushparaj Shetty; Prakash Pai (Journal of Clinical and Diagnostic Research, 2013)
Background: Oral rinse is a novel method that can be used to detect dysplasia in potentially malignant disorders and malignant oral lesions in resource challenged areas. A study was undertaken to compare the quality of the normal smears prepared with the oral rinse and that of the wooden tongue spatula. Material and Methods: One hundred five normal subjects were selected for the study. Two smears were prepared from clinically normal mucosa using an oral rinse and further two smears were scraped from clinically normal buccal mucosa using a wooden spatula. Statistical Analysis: The smears were graded for cell yield, dispersion and cellular clarity on a three-point scale by two observers. The results were analyzed using Mann Whitney non parametric test. Results: The Oral rinse was found to be significantly more efficient than the wooden spatula, in terms of cell yield (p<0.0001), cell dispersion (p =.0052) and cellular detail (p<0.0001). Conclusion: The study showed that the Oral rinse is an effective method for use in exfoliative cytology of normal oral mucosa.